Association of a non-synonymous substitution in the condensin NCAPG gene with traits of eggs in laying hens - O. Yu. Barkova; M. G. Smaragdov (Вавиловский журнал генетики и селекции)
One of the most important areas of research in the biology and genetics of farmed animals is one of identification of genes controlling the expression of traits with practical importance for animal breeding. For most of these characteristic features, wide variation in gene expression in specific loci, which are called quantitative trait loci (QTL), is typical. Eggs have been researched for decades due to their importance for the reproduction of birds, as well as for its widespread use in pharmaceutical, cosmetic and food industries. Breeding hens and cross-lines is a necessary step for producing eggs with desired quality. The results of this work are recommended for use to create systems of molecular markers for marker selection of layers and obtain new lines and cross hens with larger mass eggs. Compared to existing conventional systems of selecting layers on this basis, this will eliminate the assessment of the genotype of male progeny, which will significantly reduce breeding time. The system of markers will appear as a set of primers for detection of gene alleles that have a significant impact on the characteristics as above. The use of the molecular markers of high-performance systems for direct selection on the basis of domestic chicken eggs would lead to substantial progress in biotechnology poultry and help avoid having to purchase similar systems from outside the country. The association of the condensin NCAPG gene with the egg traits of domestic chicken has been studied. Associations of the SNP alleles of the rs14491030 marker localized in exon 8 of the NCAPG gene with the trait “the weight eggs”, p < 0.001, as well as with the elastic deformation of the egg shell, p < 0.026, have been found. It has been found that a single nucleotide nonsynonymous A G substitution leads to a significant increase in egg weight. The marker SNP rs14491030 with the observed significant effect on the trait «egg weight» can be recommended for use in breeding of laying hens. Calculations of the relative fitness of genotypes of the marker SNP rs14491030  suggest natural selection for heterozygotes. The results obtained are discussed in connection with the role of the canonical condensin complex in the compaction of chromatin and segregation of chromosomes.